Relationship between Communication Skills and General Health in Nursing Students of Hamadan University of Medical Sciences - Roya Amini; Fariba Soleimani; Nahid Mohammadi; Tapak Leili (Journal of Education and Community Health)
Background and Objective: Communication skills are one of the factors that may affect the general health of the students. The aim of this study was to determine the correlation between communication skills and general health of nursing students. Instruments and Methods: This analytical-descriptive cross sectional study was carried on 320 undergraduate nursing students in Hamadan University in 2017. The students were selected by stratified random sampling method. The data gathering tools were Goldberg General Health Questionnaire (GHQ-28) and Jerabek’s communication skills, which were completed by the students through self-administration method. Independent t-test, one-way analysis of variance, Spearman correlation coefficient, multiple linear regression model and SPSS 16 software were used. Results: Most of the students (75%) had a weak general health with a mean score of 29.71±8.68. There was a negative correlation between communication skills and general health (r=-0.33, p<0.05). Also, general health had a significant relationship with all aspects of communication skills, except for the dimension of decisiveness (p<0.05). Communication skills had a significant relationship with most aspects of general health, except social function (p<0.001). There was no correlation between demographic variables and communication skills (p<0.05). Moreover, the students, whose mothers had a governmental job or were housewives, had a better score of general health (p<0.05). Conclusion: Communication skills affect mental health, including reduction of physical symptoms, anxiety and sleep disorders, social dysfunction, and depression.